Importance of epidermal lipids for proper functioning of the stratum corneum barrier - Kansky, Aleksej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1998)
Proper structure of stratum corneum (SC) is important for regulation of vital biological functions as are protection from penetration of foreign substances through the skin, protection from UV rays, abnormal transepidermal water loss (TEWL), protection from injuries, or smooth shedding of corneocytes. Two systems, the epidermal lipids (interstitial lipids of SC) and the corneocyte cell envelopes (CE) are primarily responsible for the so-called barrier function. Lipids reach the SC through the secretion of lamellar (Odland) bodies situated in the granular layer, while the CE are being formed from loricrin, involucrin as well as from other protein precursors. Barrier function is impaired in a number of skin disorders, e.g. chronic eczema, atopic dermatitis, ichthyoses, aged skin as well as in others. Clinical tests in humans and animal experiments are teaching us that the barries function maybe restored more quickly bu applying ointments and creams containing adequate mixtures of lipids.
Keywords: dermatologija; koža; lipidi; zaščita